Development and validation of an analytical method by RP-HPLC for quantification of sibutramine hydrochloride in pharmaceutical capsules - Chorilli, Marlus [UNESP]; Bonfilio, Rudy [UNESP]; Chicarelli, Renata da Silva [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Royal Soc Chemistry, 2011)
Sibutramine is a monoamine re-uptake inhibitor used for the treatment of obesity. In the present study a rapid, sensitive and economical HPLC method was developed and fully validated for analysis of sibutramine HCl in pharmaceutical capsules. HPLC analyses were carried out by using an isocratic elution mode with a mobile phase constituted by sodium phosphate buffer (pH 2.5) and methanol (30 : 70, v/v), flow rate at 1.0 mL min(-1), column temperature at 40 degrees C, UV detection wavelength at 225 nm and 20 mu L of injection volume. The validation parameters were in accordance with FDA and ICH specifications, showing accuracy, precision, selectivity, robustness and linearity from 4.5 to 19.5 mg L(-1) of sibutramine HCl. The limits of detection and quantification were 0.666 and 2.018 mg L(-1), respectively. The validated method is suitable for quality control applications and its advantages over the already existing methods are simplicity and reduced analysis time.